Qualitative and quantitative phytochemical screening and in vitro anti oxidant and anti microbial activities of Elephantopus scaber Linn. - B, Ganga Rao; Rao, Y Venkateswara; Pavani, S; Praneeth Dasari, V S (Recent Research in Science and Technology, 2012)
Preliminary phytochemical analysis and quantification of total phenols, In-vitro antioxidant and anti microbial activities of the different fractions (hydro alcoholic, hexane, ethyl acetate and methanol) of Elephantopus scaber were carried out against five selected pathogenic bacteria and three fungal species. The plant fraction possesses steroids, triterpinoids, saponins, flavonoides, carbohydrates, glycosides and oils. For total phenolic content gallic acid was taken as a standard, the ethyl acetate fraction contains rich phenolic content than other fractions and the methanol fraction shows more DPPH, superoxide and hydroxyl radical scavenging activity. In Anti-microbial activity study all fractions showed good inhibition zone against three organisms i.e., Escherichia coli, Staphylococcus aureus Klebsiella pneumonia among the other test organisms along with Candida spp (fungal organism).